1999
DOI: 10.1007/s007750050325
|View full text |Cite
|
Sign up to set email alerts
|

The pH dependence of intramolecular electron transfer rates in sulfite oxidase at high and low anion concentrations

Abstract: The individual rate constants for intramolecular electron transfer (IET) between the Mo(VI)Fe(II) and Mo(V)Fe(III) forms of chicken liver sulfite oxidase (SO) have been determined at a variety of pH values, and at high and low anion concentrations. Large anions such as EDTA do not inhibit IET as dramatically as do small anions such as SO4(2-) and Cl-, which suggests that specific anion binding at the sterically constrained Mo active site is necessary for IET inhibition to occur.IET may require that SO adopt a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
172
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(184 citation statements)
references
References 2 publications
11
172
1
Order By: Relevance
“…NADH:ferricyanide reductase activity of CbR showed a similar result, leading to the conclusion that no large conformational change occurred when the flavin of the enzyme was reduced and transferred electrons directly to an acceptor in solution. Neither of these catalytic reactions involves IET, and the absence of a viscosity effect is consistent with the concept established in studies of the impact of viscosity on IET in SOX (13,14). NaR, similar to SOX, utilizes IET in catalysis of the NAD(P)H:NaR reaction and partial reactions such as Cyt c reduction.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…NADH:ferricyanide reductase activity of CbR showed a similar result, leading to the conclusion that no large conformational change occurred when the flavin of the enzyme was reduced and transferred electrons directly to an acceptor in solution. Neither of these catalytic reactions involves IET, and the absence of a viscosity effect is consistent with the concept established in studies of the impact of viscosity on IET in SOX (13,14). NaR, similar to SOX, utilizes IET in catalysis of the NAD(P)H:NaR reaction and partial reactions such as Cyt c reduction.…”
Section: Resultssupporting
confidence: 83%
“…Furthermore, it is clear from the impact of solution viscosity on ferricyanide reductase activity that IET is the rate-limiting process in this very rapid catalytic activity of NaR. These results are similar to those found for other redox enzymes with IET from or to a Cyt b domain, such as flavocytochrome b 2 and SOX (13,14,31). Thus, the movement of Cyt b domain relative to CbR is gating the electron and proton transfer processes in MoR and holo-NaR (Scheme 2).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…the equilibrium constant, as calculated from the transient trace, see below). Extensive flash photolysis studies on native chicken SO and wild type recombinant human SO have shown that the first-order IET rate constants between the reduced Fe(II) and oxidized Mo(VI) centers depend on the following experimental conditions: solution viscosity [34,77], sulfate concentrations [78][79][80], and pH [34,78,79]; this information is important for understanding the IET mechanism in the enzymatic catalysis (see below).…”
Section: Iet In Sulfite Oxidizing Enzymesmentioning
confidence: 99%